The Amino-Terminal C/H1 Domain of CREB Binding Protein Mediates Zta Transcriptional Activation of Latent Epstein-Barr Virus - Zerby, Dennis (American Society for Microbiology, 1999)
Latent Epstein-Barr virus (EBV) is maintained as a nucleosome-covered episome that can be transcriptionally activated by overexpression of the viral immediate-early protein, Zta. We show here that reactivation of latent EBV by Zta can be significantly enhanced by coexpression of the cellular coactivators CREB binding protein (CBP) and p300. A stable complex containing both Zta and CBP could be isolated from lytically stimulated, but not latently infected RAJI nuclear extracts. Zta-mediated viral reactivation and transcriptional activation were both significantly inhibited by coexpression of the E1A 12S protein but not by an N-terminal deletion mutation of E1A (E1AΔ2-36), which fails to bind CBP. Zta bound directly to two related cysteine- and histidine-rich domains of CBP, referred to as C/H1 and C/H3. These domains both interacted specifically with the transcriptional activation domain of Zta in an electrophoretic mobility shift assay. Interestingly, we found that the C/H3 domain was a potent dominant negative inhibitor of Zta transcriptional activation function. In contrast, an amino-terminal fragment containing the C/H1 domain was sufficient for coactivation of Zta transcription and viral reactivation function. Thus, CBP can stimulate the transcription of latent EBV in a histone acetyltransferase-independent manner mediated by the CBP amino-terminal C/H1-containing domain. We propose that CBP may regulate aspects of EBV latency and reactivation by integrating cellular signals mediated by competitive interactions between C/H1, C/H3, and the Zta activation domain.